Mastering auscultation an audio tour to cardiac diagnosis - Don Michael, T. Anthony; Shaver, James A.; Media Enterprises (New York : Mc Graw-Hill, 2000)
A'cardiophonic' CD-ROM covering normal heart conditions, coronary artery disease, valvular heart, cardiomyopathies, congestive heart failure, pericardial disease, congenital heart disease, etc.
CD is available at Koleksi Media, Perpustakaan HUKM
Collaborating author's name from container.
'Tutorial guide to basic auscultation, 100 heart sounds & murmurs, auscultatory findings in common clinical conditions, clinical, echocardiographic & the therapeutic correlations'--Container.
T. Anthony Don Michael, in collaboration with James Shaver.
System requirements for PC Windows: PC compatible with Pentium 166 mHz processor; 32MB RAM; Windows 95, 98 or NT; 16 bit display color (also known as'High Color'); 640 x 480 pixel resolution; 16 bit x 44.1 kHz audio out; 8x CD-ROM drive; headphones are recommended for optimal listening.
System requirements for Macintosh: PowerPC with 166 mHz processor; 32MB RAM; MacOS 8.1; 16 bit display color; 640 x 480 pixel resolution; 16 bit x 44.1 kHz audio out; QuickTime 4 9installer included on CD-ROM; 8x CD-ROM drive; Headphones are recommended for optimal listening.
Keywords: Auscultation -- CD-ROM; Auscultation, Heart -- diagnosis methods -- CD-ROM